1997
DOI: 10.1093/oxfordjournals.aje.a009220
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Lung Function

Abstract: It has been suggested that lung function can be altered by both free radical and oxidant exposure, while antioxidant vitamin intake is positively related to lung function. However, the information on the relation of blood levels of oxidants and antioxidants to lung function is sparse. The present cross-sectional study, conducted from September 1995 to May 1996, analyzes the association between lung function measured as forced expiratory volume in 1 second (FEV1) with 1) levels of thiobarbituric acid-reactive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 55 publications
8
74
1
1
Order By: Relevance
“…In this sample of patients with chronic airflow limitation and in our previous study of healthy individuals, we found a statistically significant inverse association of glutathione and FEV 1 (Schünemann et al, 1997). We speculate that an inverse selection is meaningful, as the body attempts to compensate for lower levels of glutathione in tissues during more severe disease.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In this sample of patients with chronic airflow limitation and in our previous study of healthy individuals, we found a statistically significant inverse association of glutathione and FEV 1 (Schünemann et al, 1997). We speculate that an inverse selection is meaningful, as the body attempts to compensate for lower levels of glutathione in tissues during more severe disease.…”
Section: Discussionsupporting
confidence: 60%
“…We found a negative association of FEV 1 % and TBARS, a marker for lipid peroxidation (Schünemann et al, 1997). In the current analysis, we found a negative association of TBARS with FVC, but not with FEV 1 .…”
Section: Discussioncontrasting
confidence: 53%
“…Increasing age is highly associated with increased oxidative stress (Romano et al 2010;Schunemann et al 1997). Therefore, we anticipated that the aged lung would represent a relatively oxidized environment.…”
Section: Alf In Old Age Contains Increased Myeloperoxidase and Oxidizmentioning
confidence: 99%
“…Therefore, slow ALF turnover plus the presence of inflammatory lung and parenchymal cells can drive baseline low-grade chronic inflammation in the lung during aging (Reynolds 1987). These events result in changes in alveolar surfactant and complement production and activity, the former as a result of a change in the local oxidation state (Schunemann et al 1997). Moreover, alterations in surfactant lipid composition are predicted to negatively affect SP-A and SP-D function (Veldhuizen et al 1998), and the latter proteins can be oxidized themselves (Umstead et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Schunemann et al (1997) were the first to report an inverse correlation between plasma lipid peroxidation products and lung functions. However, the studies on the relationships between oxidant/antioxidant imbalance and pulmonary functions did not yield consistent results.…”
Section: Relationships Between Oxidative Stress and Pulmonary Functionsmentioning
confidence: 99%